Environmental and Management Control over the Submontane Grassland Plant Communities in Central Slovakia - Andrea Diviaková; Slavomír Stašiov; Radovan Pondelík; Vladimír Pätoprstý; Milan Novikmec (Diversity, 2021)
In Central Europe, submontane grassland plant biodiversity is currently threatened by management intensification as well as by the cessation and abandonment of management activities (extensive grazing and mowing). Although the vegetation of Central European grasslands has been well described by phytosociological papers, there is still a need to improve our understanding of the effect of both management and environment on species richness and community composition. We studied submontane grassland communities in Central Slovakia. Our study showed that both environmental variables and management were important for shaping the submontane grassland species richness and floristic composition. Plant species richness showed a weak negative relationship with soil pH. When grassland management types were analyzed individually, the amount of phosphorus, nitrogen, pH, and altitude were all found to be significantly correlated with plant species richness or diversity. Management type and local environmental factors (i.e., incoming solar radiation) both determined community composition.